2020
DOI: 10.1016/j.jjcc.2019.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Clinical usefulness of quantification of myocardial blood flow and flow reserve using CZT-SPECT for detecting coronary artery disease in patients with normal stress perfusion imaging

Abstract: Radionuclide myocardial perfusion imaging (MPI) allows the visualization of radiopharmaceuticals distributed throughout the myocardium in proportion to the myocardial blood flow (MBF) and this facilitates the determination of the relative blood flow in various regions of the heart. Myocardial perfusion single-photon emission computed tomography (MPS) is a widely used noninvasive technique to evaluate ischemia and to stratify risk factors in patients with known or suspected coronary artery disease (CAD) [1-3].H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
13
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 39 publications
0
13
0
1
Order By: Relevance
“…12,13 However, since the installation of a PET tracer production system involves high costs, this technology is not yet readily available in many areas around the world. 14 The introduction of high-sensitivity dedicated cardiac cadmium-zinc-telluride (CZT) SPECT cameras, allows dynamic acquisition of tomographic images suitable for assessment of radiotracer kinetics and opens up a new era for myocardial flow and flow reserve measurement using SPECT imaging. [15][16][17] CZT-SPECT can not only achieve low-dose MPI imaging, but also provide parameters for quantitative analysis of absolute MBF through fast dynamic tomography, such as stress or rest MBF and MPR.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…12,13 However, since the installation of a PET tracer production system involves high costs, this technology is not yet readily available in many areas around the world. 14 The introduction of high-sensitivity dedicated cardiac cadmium-zinc-telluride (CZT) SPECT cameras, allows dynamic acquisition of tomographic images suitable for assessment of radiotracer kinetics and opens up a new era for myocardial flow and flow reserve measurement using SPECT imaging. [15][16][17] CZT-SPECT can not only achieve low-dose MPI imaging, but also provide parameters for quantitative analysis of absolute MBF through fast dynamic tomography, such as stress or rest MBF and MPR.…”
mentioning
confidence: 99%
“…Global and regional MPR were also predictive of the extent of CAD 16 and agreed with the FFR measurements on invasive angiographs. 26 Shirashi et al 14 reported that MPR using a CZT camera can identify balanced ischemia in patients with a left main or 3-vessel disease. In patients with suspected or known CAD a relationship between MPI findings and both hyperemic MBF and MPR obtained by CZT-SPECT was found.…”
mentioning
confidence: 99%
“…1,2 The rest majority reported the ability of CZT SPECT cameras with collimators of stationary multiple pinholes or sweeping parallel holes, and with or without attenuation correction (AC). [3][4][5][6][7][8] Technical validations were properly achieved by head-to-head comparison with PET MBF quantitation on the same cohort or the diagnostic assessment for CAD utilizing coronary angiography (CAG) or factional flow reserve (FFR) as the reference standard. [3][4][5][6][7][8][9][10][11] When the relevant physical interference in dynamic SPECT images was properly corrected, RRG and CZT cameras likely performed to the same level regardless of the CZT cameras possessing additional merits from higher count rate and less scatter by higher energy resolution.…”
mentioning
confidence: 99%
“…15 Because myocardial flow reserve (MFR) or coronary flow reserve (CFR) can be relatively preserved within an acceptable range even missing AC, validation for SPECT MBF quantitation with invasive parameters (percentage of narrowed diameter in coronary artery and FFR) has been mainly focused on the single parameter, CFR (or MFR). [3][4][5][6][7][8] The importance of stress MBF is still not yet explored for SPECT MBF quantitation due to the described limitation of SPECT systems and dedicated processing software.…”
mentioning
confidence: 99%
“…Although anatomical information on the coronary arteries is indispensable for the diagnosis of CAD, an evaluation of myocardial ischemia provides more important prognostic information beyond the severity of organic coronary stenosis. The evolution of myocardial perfusion imaging has increased the value of noninvasive assessment of myocardial ischemia [4][5][6][7]. As an…”
mentioning
confidence: 99%